The effect of direct democracy on the level and structure of local taxes - Zareh Asatryan; Thushyanthan Baskaran; Friedrich Heinemann (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2014)
We study the effect of direct democracy on local taxation. Our setting is the German federal state of Bavaria, where in 1995 a state-wide referendum introduced the possibility to initiate direct democratic legislation into the local government code. Relying on a sample of all Bavarian municipalities over the period 1980-2011, we hypothesize that complementing a representative form of government with direct democratic elements leads to (i) higher local tax rates and (ii) a shift of the local tax mix from taxes with broader (property taxes) to taxes with narrower bases (business taxes). For identification, we implement selection on observables and difference-in-discontinuity designs. Our results show that both actual direct democratic activity measured by the number of initiatives and the ease with which direct democratic legislation can be implemented measured by signature and quorum requirements increase local tax rates and shift the tax mix toward taxes with narrower bases.
urn:nbn:de:bsz:180-madoc-354598
Keywords: D72; D78; H71; 330; direct democracy; taxation; regression discontinuity; Bavaria